Memory Studies and the Writing of Bengali Literary History: Cultural Consciousness, Reading Practices, and Historical Construction/ স্মৃতি অধ্যয়ন ও বাংলা সাহিত্যের ইতিহাস : সাংস্কৃতিক চেতনা, পাঠ-প্রক্রিয়া ও ইতিহাস নির্মাণ (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Memory Studies has emerged as a powerful framework in rethinking literary historiography. Literature is not merely a site of aesthetic creativity but also a repository of national identity, cultural memory, and collective experience. Theorists such as Pierre Nora, in his concept of “Lieux de Mémoire” and Paul Ricoeur, through his reflections on “Memory, History and Forgetting”, emphasize that memory acts as a central mode of reconstructing history. In the Bengali context, literary historiography has been deeply shaped by collective memory of socio - cultural religious chronological faith or practices, colonial encounters, nationalist struggles, partition trauma, and socio-political movements. This paper explores the methodological significance of ‘Memory Studies’ in rewriting Bengali literary history, examining how memory intersects with narrative, identity, and cultural consciousness. By engaging with English quotations from modern theorists alongside Bengali literary references, the paper argues that the study of memory is indispensable for constructing a dynamic, plural, and living tradition of Bengali literary history.
Keywords: Literary Historiography; Memory Studies; Cultural consciousness; reconstruction of literary historiography; colonial hangover; political and radical influences; History and Narratives